Ketidaktaatan Terhadap Penggunaan Ruang Publik Ditinjau dari Theory of Planned Behavior (ToPB) di Kota Denpasar. Studi Kasus : Taman Kota Lumintang - Anggawirya, Anak Agung Bagus Bayu; Utari, Cokorda Istri Arina Cipta; Wiguna, I Putu Adi Jaya (Jurnal Arsitektur Lansekap; Vol. 10, No. 1 April 2024DO - 10.24843/JAL.2024.v10.i01.p15, 2024)
Public space is a place utilized by the community for recurring or regular activities. Misuse of public space that deviates from established norms and regulations leads to discomfort among users and conflicts between them. This disobedience is a phenomenon rooted in various factors. The Theory of Planned Behavior asserts that attitudes influence behavior. This means that the space influences individuals to perform specific planned behaviors. This research was conducted at Lumintang City Park, Denpasar, using a qualitative research method. Data collection techniques involved field observations, interviews, and documentation. Disobedient behaviors occurring in Lumintang City Park include smoking, defacing public facilities, skateboarding, driving in the park area, sleeping on benches, littering, vending in the park area, and bringing pets. The dominant factor influencing disobedient behavior, as per the Theory of Planned Behavior, is subjective norm.